Over-activation of primate subgenual cingulate cortex enhances the cardiovascular, behavioral and neural responses to threat - Laith Alexander (Nature Portfolio, 2020)
Alexander et al. causally implicate over-activity in primate subgenual cingulate in affective and cardiovascular dysfunction relevant to anxiety and depression. Over-activation led to elevated activity in a stress-related network whilst decreasing activity in higher-order prefrontal cognitive regions.